Pengembangan Media Pembelajaran Augmented Reality Berbasis Android dengan Pendekatan Saintifik pada Materi Organ Tumbuhan - Sobri Aminolla; Ismul Mauludin Al Habib; Hanif Rafika Putri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to examine students’ responses to the implementation of Android-based augmented reality learning media using a scientific approach. The research employed a research and development (R&D) method with the ADDIE model as its development framework. The instruments consisted of interviews, observations, and assessment questionnaires completed by media, language, and material validators, as well as students. Data were analyzed descriptively, both qualitatively and quantitatively. The results showed that the developed learning media were considered feasible based on expert evaluations and student responses. In conclusion, the Android-based augmented reality learning media proved effective in enhancing students’ understanding of plant organ material. Keywords: Augmented Reality, Development, Learning Media